2015
DOI: 10.1680/jensu.14.00067
|View full text |Cite
|
Sign up to set email alerts
|

Can bicycle training for children increase active travel?

Abstract: Evidence in support of cycle training is limited, and its potential to improve safety and make a tangible difference to cycling levels is unclear. Nevertheless, Bikeability, the UK government's cycle training programme introduced in 2006, is widespread in schools and is actively supported by many parents/carers. This paper draws together a number of evidence sources in an attempt to understand the role of cycle training as one among several measures for increasing active travel. It reviews existing research re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Results are presented at the intervention level because three papers reported the findings of two different interventions. Specifically, Buckley et al [ 29 ] included a fall event without control group and a spring event with control group, Crawford and Garrard [ 34 ] included a pilot study with control schools (pilot schools) and a main study without control group (program schools), and Johnson et al [ 41 ] reported case-control analyses using data from two different surveys conducted in distinct populations (Bikeability and CensusAtSchool). Eleven interventions were conducted in the US, five in the UK, three in Canada, two in Australia, Belgium, Denmark and New Zealand, and one in Spain and China.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results are presented at the intervention level because three papers reported the findings of two different interventions. Specifically, Buckley et al [ 29 ] included a fall event without control group and a spring event with control group, Crawford and Garrard [ 34 ] included a pilot study with control schools (pilot schools) and a main study without control group (program schools), and Johnson et al [ 41 ] reported case-control analyses using data from two different surveys conducted in distinct populations (Bikeability and CensusAtSchool). Eleven interventions were conducted in the US, five in the UK, three in Canada, two in Australia, Belgium, Denmark and New Zealand, and one in Spain and China.…”
Section: Resultsmentioning
confidence: 99%
“…Year 6 students who received Bikeability expressed greater confidence (OR = 1.81; 95% CI = 1.26-2.59). None examined Johnson et al 2016 [ 41 ] England [CensusAtSchool] Bikeability , a national cycle training program for children and adults. Strategies: education only.…”
Section: Methodsmentioning
confidence: 99%
“…NCPS training was not available in all schools, and this remains the situation today. It is estimated that in 2013/2014 only around half of primary schools offered Bikeability training, and these schools are not evenly distributed across the country [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, two studies that compared cycling rates in trained and untrained children did not have such positive results. One used two datasets to assess children’s cycling behaviour, and found a positive association with Bikeability training in one dataset but not the other [ 19 ]. The other study found that two months after the course finished, the trained children did not report cycling more frequently than the untrained children, despite reporting that training had made them feel more confident about cycling on the road [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation